Prediction and Inferred Evolution of Acid Tolerance Genes in the Biotechnologically Important Acidihalobacter Genus - Boase, Katelyn; González, Carolina; Vergara, Eva; Neira, Gonzalo; Holmes, David; Watkin, Elizabeth (Frontiers in Microbiology, 2022)
Acidihalobacter is a genus of acidophilic, gram-negative bacteria known for its ability to oxidize pyrite minerals in the presence of elevated chloride ions, a capability rare in other iron-sulfur oxidizing acidophiles. Previous research involving Acidihalobacter spp. has focused on their applicability in saline biomining operations and their genetic arsenal that allows them to cope with chloride, metal and oxidative stress. However, an understanding of the molecular adaptations that enable Acidihalobacter spp. to thrive under both acid and chloride stress is needed to provide a more comprehensive understanding of how this genus can thrive in such extreme biomining conditions. Currently, four genomes of the Acidihalobacter genus have been sequenced: A. prosperus DSM 5130T, A. yilgarnensis DSM 105917T, A. aeolianus DSM 14174T and A. ferrooxydans DSM 14175T. Phylogenetic analysis shows that the Acidihalobacter genus roots to the Chromatiales class consisting of mostly halophilic microorganisms. In this study, we aim to advance our knowledge of the genetic repertoire of the Acidihalobacter genus that has enabled it to cope with acidic stress. We provide evidence of gene gain events that are hypothesized to help the Acidihalobacter genus cope with acid stress. Potential acid tolerance mechanisms that were found in the Acidihalobacter genomes include multiple potassium transporters, chloride/proton antiporters, glutamate decarboxylase system, arginine decarboxylase system, urease system, slp genes, squalene synthesis, and hopanoid synthesis. Some of these genes are hypothesized to have entered the Acidihalobacter via vertical decent from an inferred non-acidophilic ancestor, however horizontal gene transfer (HGT) from other acidophilic lineages is probably responsible for the introduction of many acid resistance genes.